Altorientalische Notizen (31-44) - Bauer, Josef (1987)
31. ud5, ùz oder ùzu(d)? 32. GÍR = šumx. 33. múrgu. 34. ur?kum. 35. ASARI = banšurx. 36. *?urin = "Zeder"? 37. Ein Gefäß in 5 Schreibungen? 38. dŠAGAN-šeg9-bar. 39. ZIZI.Š